Solution for an Irregular Perturbation Problem of Viscoplastic Spherical Container Under Internal Pressure - Wojno, W. (Engineering Transactions, 1993)
An irregular perturbation problem around a quasi-static solution for a motion of a thick-walled spherical container made from viscoplastic material and subjected to a time-dependent internal pressure is dealt with. Only the first perturbations are taken into account. A practically important case of a power excess stress function above the static yield stress is considered.